Keep calm in a crisis: Best practices for emergency scheduling. Issue 3 (May 2016) - Sutton, Halley
Abstract : ANAHEIM, CALIF. — In the winter of 2013, Oregon State University experienced a major snowstorm at the beginning of finals week, closing campus for two days. A total of 700 finals had to be rescheduled; five days of finals had to be compressed into three, and 18, 000 students were impacted directly by the rescheduling. The Registrar's Office was given 48 hours to reschedule all finals, a process that usually takes more than two weeks.